Preventing recession in Europe: National vs. European approaches - Holger Schmieding; Daniel Gros; Tito Boeri; Ansgar Belke (Intereconomics, 2009)
Policymakers in the EU member states are currently shaping rescue packages to prevent the financial crisis hitting their economies with unmitigated force. Each government is responding to the emerging problems with a country-specific set of measures. Given the global nature of the crisis, would coordinated action at the European level not be a better approach? Was the German government much-criticised for its initial reluctance to adopt massive fiscal stimulation measures right after all to exploit the option value of waiting in a situation of high uncertainty?
Keywords: 330